2014
DOI: 10.5152/tjg.2014.5603
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of hepatic ultrasound, liver biopsy, and duodenal tube test in the diagnosis of extrahepatic biliary atresia in Serbian infants

Abstract: Background/Aims: Extrahepatic biliary atresia (EHBA) is the most important cause of neonatal cholestasis. The validity of different diagnostic methods in the diagnosis of EHBA in developed countries has been presented elsewhere, but data from developing countries with low national incomes are scarce. The aim of this study was to investigate the relative accuracy and roles of abdominal ultrasonography, duodenal tube test (DTT), and liver biopsy in the diagnosis of EHBA in Serbia. Materials and Methods: The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…9,10,15,17 Liver biopsy remains the gold standard for differentiating causes of neonatal cholestasis with high sensitivity and specificity. 9,14,18 In the present study, concordant with the literature, 21 (28%) of the 75 patients had BA, 54 (72%) had NH with 29 (39%) of them were idiopathic. Previous studies showed that infants with NH had variable prognosis, but in 60% to 70% of cases liver functions might return to normal ranges with optimal nutritional support.…”
Section: Discussionsupporting
confidence: 90%
“…9,10,15,17 Liver biopsy remains the gold standard for differentiating causes of neonatal cholestasis with high sensitivity and specificity. 9,14,18 In the present study, concordant with the literature, 21 (28%) of the 75 patients had BA, 54 (72%) had NH with 29 (39%) of them were idiopathic. Previous studies showed that infants with NH had variable prognosis, but in 60% to 70% of cases liver functions might return to normal ranges with optimal nutritional support.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is critical to establish reliable models for the early detection and diagnosis of BA. Unfortunately, the definitive diagnosis and confirmation of BA in suspected infants generally requires a liver biopsy and intraoperative cholangiography (IOC) during the surgical procedure, and these diagnostic methods have turned out to be invasive, time-consuming, and costly [ 6 , [17] , [18] , [19] , [20] ]. Obviously, there is an urgent need for a reliable and better diagnostic approach to distinguish BA from other form of neonatal cholestasis (NC) with different causes.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to results of others who found a sensitivity of 97% and NPV of 93 or 98.6% if bile fluid was present. 16,17 In our study, infants diagnosed with BA had GGT levels that were about twice as high as in patients with other cholestatic liver diseases. This is in accordance with other studies 18,19 who also found higher GGT concentrations.…”
Section: Discussionmentioning
confidence: 46%
“…Scoring systems to assess the risk of BA have been developed, but they involve taking liver biopsies. 16,[33][34][35] We have developed a scoring system without risky interventions. It may be helpful in centers that do not have the expertise with this rare disease and that do not have the specialists to perform ERCPs in infants.…”
Section: Discussionmentioning
confidence: 99%